Peran Penasehat Hukum dan Organisasi Profesi Advokat Untuk Memastikan Terjaga Hak Hak Normatif Narapidana - Irawan, Hilmi Dwi; Subrata, Rusli (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research investigates the practice of providing legal aid by legal counsel to prisoners in the context of ensuring that the normative rights of prisoners are implemented. Using a qualitative approach with an empirical juridical approach, this study gained in-depth insights into the role of legal counsel, the challenges faced, and the impact on prisoners. Through interviews, observations, and document analysis, the research findings highlight a number of challenges faced by legal counsel, including legal uncertainty, social stigma, and unequal access to legal resources. However, this research also shows that legal counsel and advocate organizations have a crucial role in ensuring that prisoners continue to have equal access to justice. The results of this study provide a better understanding of the practices of legal counsel and Advocate Organizations in providing legal aid to prisoners and their impact on justice and access to the law. The implications of this research emphasize the importance of cooperation between legal counsel, advocate organizations, government, and civil society organizations in improving the effectiveness of the system of providing legal aid to prisoners. By maintaining a commitment to the principles of justice and human rights, it is hoped that the results of this study can make a positive contribution to efforts to maintain justice for prisoners in the future.